Three laws for paperlessness. (January 2019) - Thimbleby, Harold
We are familiar with paper and rarely think much about it, except that in healthcare there seems to be too much of it, and it is slow, inefficient, and so old. In contrast, paperlessness promises the future and freedom from paper's obvious limitations. We need to think clearly how to ensure paperlessness really improves healthcare, hence three simple laws: 1. Keep in sight the goal of improving healthcare. Paperlessness must be first about improving clinical processes, supporting staff and patients, not about replacing paper with new 'solutions'. 2. Only implement evidence-based change. Pursue paperlessness only where there is scientific evidence it is better for the real task. Successful paperlessness depends on user centred design and on quality implementation. 3. Plan for cultural change and moving goal posts. Culture has to change to take advantage of technology, and technology is changing at pace regardless. Paperless requires planning for monitoring, improvement, revision and, eventually, obsolescence and further innovation. Pay attention to culture, including regulation, and to developing human skills to exploit new technologies.